Islamic Premarital Guidance and Counseling to Enhance Students Readiness to Marriage - Sugandhi, Nani M; Yusuf, Syamsu; Nurihsan, Juntika; Riyadi, Arie R (Universitas Muhammadiyah Metro, 2021)
This study aims to develop the readiness of college students to build family well-being (marriage). In particular, this study produced a model based on the construct of student readiness to get married. The research uses research and development methods. The research procedures were carried out starting from field trials to obtain empirical results. The sample involved 267 students from six public and private universities in the city of Bandung. The results of the study obtained a high impact on students' readiness in marriage.